Differences in Length of Hospital Stay for COVID-19 Patients Given Combination Supplementation of Vitamins C, D, and Zinc: A Clinical Nutrition Perspective: Perbedaan Lama Waktu Rawat Inap Pasien Covid 19 yang Diberi Suplementasi Kombinasi Vitamin C, D, dan Zink: Tinjauan Aspek Gizi Klinis - Syah, Farid Zulkarnain Nur; Fidyasari, Ambar (jurnal makanan tropis dan teknologi agroindustri, 2025)
COVID-19 has placed a substantial burden on global healthcare systems. Nutritional improvement through dietary supplementation with vitamin C, vitamin D, and zinc plays a critical role in supporting the immune system. This study aimed to evaluate the effect of combined supplementation with vitamins C, D, and zinc on the length of hospital stay in COVID-19 patients. This study employed a retrospective observational design conducted in a hospital setting. A total of 81 patient were included as research subjects. The majority of patients were aged 50–64 years (45.7%) and female (51.9%). Data were analyzed using the Kruskal–Wallis test, followed by post hoc analysis. The results showed that the group receiving the combined supplementation of vitamins C, D, and zinc had the shortest average hospital stay (10.00 ± 4.299 days), compared to the vitamin D group (12.29 ± 4.165 days) and the vitamin C and D group (12.69 ± 2.869 days), with a statistically significant difference (95% CI; p = 0.004). This study concludes that the combination of the three micronutrients (vitamins C, D, and zinc) significantly reduces the duration of hospitalization in COVID-19 patients compared to those receiving vitamin D alone or a combination of vitamins C and D.